When Justice Fails to Matter: Judicial Independence and Economic Freedom in Western Balkan Countries - Spahiu, Muhamet; Gordani, Lorenc; Durguti, Esat A.; Tmava, Qazim (Ekonomika, 2026)
This study empirically investigates the factors associated with economic freedom, enabling governmental leadership structures to take preventive measures against factors that undermine economic freedom and further promote its strengthening. Our research aims to identify the factors that influence the establishment or promotion of economic freedom, by considering variables such as judicial independence, property rights, the gender diversity index, the legal enforcement of contracts, and regulatory trade barriers. The data applied in this research cover the period from 2010 to 2023, employing a panel data regression. The study’s findings indicate that property rights, the gender diversity index, and regulatory trade barriers have a significant influence on economic freedom, whereas the legal enforcement of contracts has a significant negative influence. A particularly challenging result emerged regarding judicial independence, as it was found to have a statistically insignificant influence. The empirical discoveries presented in this research have significant implications for policymakers in the analyzed countries. Furthermore, the results provide valuable insights for policymakers regarding the improvement of existing national policies and addressing deficiencies that may negatively affect economic freedom.